A companion to the French Revolution - McPhee, Peter, 1948- (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, 2013)
Comprises newly-written essays reassessing the origins, development, and impact of this great turning-point in modern history. Examines the origins, development and impact of the French Revolution Features original contributions from leading historians, including essays translated from French. Presents a wide-ranging overview of current historical debates on the revolution and future directions in scholarship. Gives equally thorough treatment to both causes and outcomes of the French Revolution.
Introduction / Peter McPhee -- pt. I. The origins and nature of the crisis of 1789 -- pt. II. Reshaping France, 1789-91 -- pt. III. Church, state, and war -- pt. IV. Contesting the limits of revolution -- pt. V. Revolutionary and counter-revolutionary violence -- pt. VI. Political choice and practice -- pt. VII. Searching for stability, 1794-99 -- pt. VIII. The revolution in international perspective -- pt. IX. Change and continuity in France.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: 1789-1799; France -- History -- Revolution, 1789-1799.; HISTORY -- Europe -- France; Historiography; France -- History -- Revolution, 1789-1799 -- Historiography; France -- History -- Revolution, 1789-1799.; France; Electronic books; History